SISTEM INFORMASI GEOGRAFIS PENCARIAN JALUR TERPENDEK TEMPAT PENGINAPAN DI SURABAYA MENGGUNAKAN ALGORITMA DIJKSTRA - Rimala Dewi, Linda; Dwi Satoto, Budi (Proceedings of KNASTIK, 2012)
On business or vacation travelling to outside city, it's need to take a rest for a while.Aim of this purpose travelling is begining from departure places that it's need to knowshortest and fastest path that belong to correct way to the destination places. Todetermine this shortest path, user have to know the route to reach any place from map.Although Surabaya is one of the big city, this city devide into five region and 31 districtthat define in Google map, Geographic Information system with shortest path finddestination place such rest place, Lodging house in this city is become recommend forthis new traveller. Dijkstra algorithm used to find shortest path very helpfully to solvetraveller problem although worst condition such as weather problem, missing path anddirection or etc. This application support with web base application that can be surffrom Handheld phone that very simple to used. This SIG with google map also expectedto help new traveller getting shortest path similar with his speed of driving.